2020
DOI: 10.1177/0971333620943408
|View full text |Cite
|
Sign up to set email alerts
|

Ageing in Developing Societies: Issues and Challenges

Abstract: Ageing has emerged as a major challenge in several developing societies. With falling fertility rates and increasing longevity as its main drivers, it is expected that by 2050, one in five people of the developing countries will be over 60 years of age. It is argued that on account of this, such societies would further encounter an increased demand for medical treatment, long-term care, financial and emotional support. They also are likely to face an enormous psychological burden. In the context of ageing, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Remedy strategies for ageing welfare leaking have been proposed: (1) social security system: [7] found that retirement is a major problem for vulnerable families in Macau. Thus, improving the social security system to society's future retirement security needs is important.…”
Section: Remedy Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Remedy strategies for ageing welfare leaking have been proposed: (1) social security system: [7] found that retirement is a major problem for vulnerable families in Macau. Thus, improving the social security system to society's future retirement security needs is important.…”
Section: Remedy Strategiesmentioning
confidence: 99%
“…The goal is to create community-based non-formal lifelong learning opportunities for developing inclusive, equitable, and caring active ageing societies. (7) Legal system: the law provides a benchmark to protect and promote an age-friendly environment [33]. (8) Population policy: China has announced a new population policy for encouraging reproduction and having multiple children in the family to solve the foreseeable economic development and ageing welfare issues [34].…”
Section: Remedy Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of aging is perceived in multiple ways including chronological age and biological markers such as impairment in vision and hearing, wrinkling skin, and fatigue, who represent the fastest-growing segment of populations throughout the world. However, families and communities often use other sociocultural referents to define age, including family status (grandparents), physical appearance, or age-related health conditions (Kohli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Demographic projections have confirmed that more older persons are expected to live in developing countries (Kohli et al, 2020;Lloyd-Sherlock, 2000;Shetty, 2012). This exposes them to life in conditions of extreme poverty, marginalization, and vulnerability in absence or lack of proper policy response and erosion in the traditional forms of support structure.…”
Section: Introductionmentioning
confidence: 99%